Panel Measuring Instruments for Power Electronics - Askarbek K. Karmyshakov; Zhalalidin T. Galbaev; Fozildjon A. Khoshimov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: The relevance of the work is due to the need to improve the accuracy of electrical measurements and visualization of instrument readings through new circuit solutions. To ensure the reliability, safety and efficiency of power electronic systems, accurate measurements of various electrical parameters are required. This article discusses the types of measuring instruments used in power electronics, their characteristics and scope of application. Particular attention is paid to digital panel meters (DPM), which, compared to analog solutions, have a number of technological, operational and economic advantages. Aim: improve the accuracy and visibility of electrical measurements using new circuit design solutions. Methods: When developing the laboratory complex, methods of electronic process modeling were used using the software environments Multisim, Proteus VSM, Micro-Cap, as well as methods of modeling and prototyping. When studying mathematical models of electrical equipment components, the MatLab application software package was used. Results: laboratory complexes for studying elements and devices of power electronics were developed and manufactured, where indicator panels designed by the authors using new circuit solutions were used.